Understanding Second Language Process - Han, ZhaoHong (Second Language Acquisition, 2007)
This book assembles 11 analytical and empirical studies on the process of second language acquisition, probing a wide array of issues, from transfer appropriate processing to L2 default processing strategies, among hearing or deaf learners of a variety of target languages including English, Japanese, Chinese, Korean, French, Spanish, and American Sign Language. Although instruction per se is not the focus of this volume, the chapters are written with instructed learners in mind, and hence offer valuable insights for both second and foreign language researchers and practitioners